Waterscape of belonging: symbolic water infrastructure, governance legitimacy, and urban identity in Shanghai - Qi, Yuanbo; Huang, Panpan (Frontiers in Environmental Science, 2025)
Urban expansion in rapidly developing regions increasingly relies not merely on technical infrastructure but on symbolic spatial design as a means of identity construction. This study investigates how Shanghai’s regenerated waterscapes operate as symbolic infrastructures that shape public perceptions of governance and belonging. Drawing on 36 in-depth interviews and thematic analysis, the research examines citizens’ interpretations of revitalized canals, eco-corridors, and digital water systems. The findings indicate that three-quarters of participants (75.0%) embed biographical memory and local belonging into regenerated waterscapes, whereas an even larger share (80.6%) interprets governance through ritualized maintenance, signage, and visible responsiveness. This study concludes that these symbolic attachments enable water infrastructure to legitimize state authority and reinforce social cohesion in contemporary China.